Stereoselective aromatic ring hydrogenation over supported rhodium catalysts in supercritical carbon dioxide solvent - Shirai, M.; Hiyoshi, N.; Rode, C. V. (Chemical Record, 2019)
The combination of supported rhodium metal catalysts and supercritical carbon dioxide solvent was effective for the stereoselective ring hydrogenations of aromatic compounds at low temperature. Higher solubility of hydrogen in supercritical carbon dioxide provides higher concentration of hydrogen on the rhodium surface, but lower that of the intermediate on rhodium surface, which suppresses the flipping of surface intermediate, leading to higher catalyst activities and cis selectivities to the corresponding ring-hydrogenated products as compared with those in organic solvents.